Anatomy and embryology teaching models: articles and patents technological monitoring, accessibility and inclusion (Olhar de Professor, 2022)
Educational inclusion aims at the participation of students with disabilities through modifications in education turning it as accessible so that equal opportunities are obtained. In this perspective, the use of inclusive teaching models is a promising alternative. Thus, the present work aimed to do technological monitoring of teaching models in anatomy and embryology that are inclusive to visually impaired students. Then, a technological monitoring of didactic models on anatomy and embryology was carried out in national and international articles and patents bases. Based on the results obtained, it can be concluded that although the use of teaching models is satisfactory in aiding the teaching and learning process, the development of teaching models of anatomy and embryology is still scarce, especially the inclusive ones.
Keywords: Inclusive education. Technological monitoring. Teaching of biology.